Correlation of Maxillary Intercanine Distance with Interalar Width in Dentate Subjects - Aima Riaz; Salman Ahmad; Sara Urooj; Sana Afzal; Ayesha Mehak Saeed; Kiran, Pakeeza (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine the correlation of maxillary intercanine distance with interalar width in dentate candidates. Study design: Cross-Sectional study Study place and duration: Department of Prosthodontics, Foundation University College of Dentistry, Islamabad, Pakistan, from Oct 2024 to Mar 2025. Methodology: A total of 110 candidates with fully erupted natural maxillary and mandibular anterior teeth and Angle Class-I occlusion were enrolled. In order to measure the interalar width, two points were marked on the widest area of right and left alae of nose with the help of indelible pencil and distance between both points was measured with Digital Vernier Caliper Intercanine distance was measured from right to left canine cusp tip using the same vernier caliper. Results: The mean age of participants was 20.58±1.88 years, with 54(49.1%) males and 56 (50.9%) females. The mean interalar width was 35.65±4.91 mm, and the mean intercanine distance was 38.22±2.48 mm. A positive correlation was found between interalar width and intercanine distance (r = 0.556, p=<0.001), though it was neither strong nor weak overall. Agespecific analysis showed a weak correlation in subjects <20 years (r = 0.486, p=0.002), and a stronger correlation in those >20 years. Gender-wise, a stronger correlation was noted in females (r = 0.686, p=<0.001) compared to males (r = 0.510, p=<0.001). Conclusion: A positive but weak correlation exists between interalar width and intercanine distance in young dentate subjects.